Search for a Resonance Decaying into WZ Boson Pairs in p(p)over-bar Collisions - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (Amer Physical Soc, 2010)
We present the first search for an electrically charged resonance W' decaying to a WZ boson pair using 4.1 fb(-1) of integrated luminosity collected with the D0 detector at the Fermilab Tevatron p (p) over bar collider. The WZ pairs are reconstructed through their decays into three charged leptons (l = e, mu). A total of 9 data events is observed in good agreement with the background prediction. We set 95% C.L. limits on the W'WZ coupling and on the W' production cross section multiplied by the branching fractions. We also exclude W' masses between 188 and 520 GeV within a simple extension of the standard model and set the most restrictive limits to date on low-scale technicolor models.